Insights into protein recognition for γ-lactone essences and the effect of side chains on interaction via microscopic, spectroscopic, and simulative technologies. (25th April 2019) - Sun, Qiaomei; Gan, Na; Zhang, Shuangshuang; Zhao, Ludan; Tang, Peixiao; Pu, Hongyu; Zhai, Yuanming; Gan, Ruixue; Li, Hui
Highlights: Molecular recognition between γ-lactone essences and human serum albumin were studied. The morphology of HSA changed induced by interactions with ligands. Ligands had weak binding with HSA, causing slight protein second structural changes. Binding ability and secondary structure changes were positively correlated with side chain length. Side chain length affected the binding by steric hindrance and hydrophobicity. Abstract: The binding properties between γ-lactone essences and HSA were investigated to explore interactional mechanism and influence of ligand side chains on binding via computer simulations, microscopy, and multiple-spectroscopies. Docking and molecular dynamics presented protein recognition mode with low fluctuations. NMR analysis revealed that the lactone ring of ligands was the main group bound to HSA. UV–vis and lifetime results revealed that the combination was static quenching mechanism with binding constants of 10 2 –10 3 L/mol. FTIR and CD spectra showed conformational changes in the protein secondary structure induced by ligands. Side chains affect the binding process through steric hindrance and hydrophobicity. AFM images showed the four compounds caused different effects on molecular size of HSA. In conclusion, the binding ability and the protein secondary structure changes had a positive correlation with the length of side chain. These studies are beneficial for understanding the safety and biological action of γ-lactone essences.